1999
DOI: 10.1046/j.1365-2672.1999.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax toxin fusion proteins for intracellular delivery of macromolecules

Abstract: The dominant role played by the anthrax toxin in Bacillus anthracis pathogenesis shows that the toxin has evolved to be an efficient system for delivering its two catalytic protein components, oedema factor and lethal factor (LF), into the cytosol of host cells. This system involves binding of the protective antigen (PA) toxin component to a ubiquitous (and still unidentified) receptor, proteolytic activation at the cell surface, internalization by endocytosis and translocation through an early endosome membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…A possible explanation for why rPA preparations rich in more negatively charged isoforms are less biologically active in vitro may be the improper folding of one or more of the four functional domains. Elucidation of the extent of deamidation within each of the rPA domains, i.e., receptor-binding domain, or lethal/edema factor binding domain [30][31][32][33][34][35][36], may provide additional information, but is beyond the scope of this report. GMP grade rPA does not contain the more negatively charged isoforms present in the R&D grade material, which resulted in observable differences in biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for why rPA preparations rich in more negatively charged isoforms are less biologically active in vitro may be the improper folding of one or more of the four functional domains. Elucidation of the extent of deamidation within each of the rPA domains, i.e., receptor-binding domain, or lethal/edema factor binding domain [30][31][32][33][34][35][36], may provide additional information, but is beyond the scope of this report. GMP grade rPA does not contain the more negatively charged isoforms present in the R&D grade material, which resulted in observable differences in biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage occurs at a surface loop and releases PA 20 , the N-terminal fragment of PA. Loss of this N-terminal fragment results in self-association of PA 63 , the C-terminal fragment of PA, forming membrane-inserting heptamers capable of binding LF and/or EF (20). These complexes are taken up into cells and enter the lumen of the acidic endosomal compartment, from which LF emerges to initiate enzymatic reactions that ultimately result in cell death (1,12,15).Through the use of combinatorial chemistry techniques, workers in our laboratory have developed the compound hexa-D-arginine (D6R) as a potential therapeutically useful furin inhibitor (4). Studies that used Pseudomonas aeruginosa exotoxin A (PEA), a bacterial toxin which also requires furin processing, have shown that D6R effectively blocks PEA-induced cell death in vitro and in vivo (21).…”
mentioning
confidence: 99%
“…Cleavage occurs at a surface loop and releases PA 20 , the N-terminal fragment of PA. Loss of this N-terminal fragment results in self-association of PA 63 , the C-terminal fragment of PA, forming membrane-inserting heptamers capable of binding LF and/or EF (20). These complexes are taken up into cells and enter the lumen of the acidic endosomal compartment, from which LF emerges to initiate enzymatic reactions that ultimately result in cell death (1,12,15).…”
mentioning
confidence: 99%
“…The prognosis of patients with advanced and metastatic MM is poor. [1][2][3] Approximately 3000 new cases are reported each year in the United States, and more than 10 000 are reported worldwide. 2,4 As mesothelioma symptoms do not arise until late stages, the majority of mesothelioma patients are diagnosed in an advanced stage of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Approximately 3000 new cases are reported each year in the United States, and more than 10 000 are reported worldwide. 2,4 As mesothelioma symptoms do not arise until late stages, the majority of mesothelioma patients are diagnosed in an advanced stage of malignancy. 5 MM is resistant to all currently available treatments; therefore, understanding the mechanisms involved in the growth of MM may provide insights for the development of new therapeutic strategies to treat patients with MM.…”
Section: Introductionmentioning
confidence: 99%